A67 An Innovative, Sustainable Paediatric Knowledge and Skills Session for Early-Year Medical Students: Boosting Student Confidence and Clinical Knowledge - Meherun Rahman; Emma Vickers; Nicola Watts; Louise Harmer (Journal of Healthcare Simulation, 2025)
Introduction: Medical students repeatedly report a lack of confidence in their paediatric knowledge and clinical skills, which can adversely affect their learning experience [1]. Given the complexity and nuances of Paediatrics, coupled with limited placement exposure, creative and accessible teaching interventions are imperative [2]. This service evaluation aimed to assess whether delivering a dedicated Paediatric Knowledge and Skills Session (PKSS) early in training could improve student confidence and knowledge, while remaining sustainable and easily replicable. Methods: This service evaluation was created and delivered by a multi-disciplinary team of clinical educators and immersive technology experts at a teaching hospital. The PKSS included gamification, simulation, interactive quizzes, and lecture-based teaching within a single-day, providing an engaging yet challenging experience. It was designed with sustainability in mind, using existing departmental manikins, donated clinical equipment (e.g., non-rebreather masks, blood bottles), and recycled or reusable materials for games with no ongoing costs. Quizzes were delivered electronically to minimise paper use. Sessions were facilitated by educators experienced in paediatrics or simulation, requiring minimal staff training resources. Students completed digital pre- and post-session MCQs, self-rated confidence surveys, and qualitative feedback forms. Results: Of the 28 participating students, data from 22 were analysed due to incomplete or unmatched responses. The 22 students showed significant improvement in confidence across all items, with 5 questions reaching extreme statistical significance (p